Food challenge and community-reported reaction profiles in food-allergic children aged 1 and 4 years: A population-based study - Chan, J; Peters, R; Koplin, J; Dharmage, S; Gurrin, L; Wake, M; Tang, M; Prescott, S; Allen, K; Healthnuts Study,; Dwyer, T (Elsevier, 2017)
Background Oral food challenge is the main tool for diagnosing food allergy, but there is little data on the reaction profiles of young children undergoing challenges, nor how these reactions compare to reactions on accidental ingestion in the community. Objectives To compare reaction profiles from food challenges and parent-reported reactions on accidental ingestion, and assess predictors of severe reactions. Methods HealthNuts is a longitudinal population-based cohort study of 5276 1-year-old infants. Infants underwent skin prick tests and those with identifiable wheals were offered food challenges. Food challenges were repeated at age 4 years in those with previous food allergy or reporting new food allergies. Community-reported reactions were ascertained from parent questionnaires. Results Food challenges were undertaken in 916 children at age 1 year and 357 children at age 4 years (a total of 2047 peanut, egg, or sesame challenges). Urticaria was the most common sign in positive challenges at both ages (age 1 year, 88.7%, and age 4 years, 71.2%) although angioedema was significantly more common at age 4 years (40.1%) than at age 1 year (12.9%). Anaphylaxis was equally uncommon at both ages (2.1% and 2.8% of positive challenges at ages 1 and 4 years, respectively) but more common for peanut than for egg (4.5% and 1.2% of positive challenges at ages 1 and 4 years, respectively). The patterns of presenting signs reported during community reactions were similar to those observed in formal food challenges. Serum food-specific IgE levels of 15 kU/L or more were associated with moderate to severe reactions but skin prick test was not. Conclusions There was a shift from the most common presenting reaction of urticaria during food challenges toward more angioedema in older children. Serum food-specific IgE levels were associated with reaction severity.